A Study on the Impact of Taglines on Consumers in the Non-Alcoholic Beverages Segment - Devarai, K.; Shetty, Deepli (SFIMAR Research Review, 2010)
The Non-alcoholic beverages segment in India is one such segment which is signified by frequent change of taglines. As such the challenge lies how fast consumers can forget the old tagline and associate new tagline with the product. One hears the tagline of any company and his/her mind associates it with product Pepsi with prior exposure to this associations in the form of T.V. commercials or Print media. This is the power of tagline. It expresses an enduring idea that reveals the crux of your brand message and illustrates the value of doing business with you. Ultimately, think of your tagline as a final point that wraps up your 30-second elevator pitch. This paper aims at determining whether taglines in this segment have an impact on Consumers by enhancing brand awareness and recall. Also determining whether taglines enhance product preference and drive consumers to make a purchase. The study unveils that for the products like Limca, Thumps up, and Boost whose taglines remained unchanged for a longer period showed high brand awareness and brand recall. On the other hand Products like Sprite, Fanta, and Bru whose taglines are changed frequently showed low brand awareness and brand recall. And Pepsi’s "Yeh dil maange more" is the most favorite tagline among consumers. Yet another finding of this study is that Wordings and the advertisement theme of a tagline appeals the most to consumers and majority of the respondents came across their favorite tagline through TV.Commercials and also it was found that majority of the respondents feel that they were never influenced by tagline to make purchase however there is a possibility that taglines may be working sublimely in their mind and they are unaware of it. An associated finding is that the chance of getting greater Brand awareness using taglines in local language is low in the Non-alcoholic beverages segment.